Measurement of the B0s→μ+μ− decay properties and search for the B0→μ+μ− and B0s→μ+μ−γ decays; Physical Review D; Vol. 105, iss. 1 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Vagner A. R. Aleksandr Rudolfovich (2022, 2022)
Title screen